Identifying prospective memory deficits in multiple sclerosis: Preliminary evaluation of the criterion and ecological validity of a single item version of the memory for intentions test (MIST). Issue 2 (17th February 2023) - Gromisch, Elizabeth S.; Turner, Aaron P.; Neto, Lindsay O.; Haselkorn, Jodie K.; Raskin, Sarah A.
Abstract: Objectives: Difficulties with prospective memory (PM) are not routinely assessed in persons with multiple sclerosis (MS) even though they can impact daily functioning. This study aimed to examine the preliminary criterion and ecological validity of a highly abbreviated Memory for Intentions Test (MIST) intended to serve as an initial screening of PM in persons with MS. Methods: Participants (n = 112) were classified as impaired if they performed 1.5 standard deviations below the normative mean on the MIST. Individual MIST trials with adequate difficulty and discriminability were examined using receiver operating characteristic analyses, with their classification accuracies, sensitivities, and specificities compared to each other. Regressions were run to evaluate their ecological validity, with appointment attendance and employment as the outcomes. Results: Two trials had a classification accuracy of ≥80%: Trial 3 (79% sensitivity, 84% specificity) and Trial 4 (57% sensitivity, 91% specificity). These two trials had comparable specificity (p=.127), with Trial 3 having slightly higher sensitivity (p=.083). Only Trial 4 was significantly associated with appointment attendance (b = 1.63, p=.047) and unemployment (aOR = 11.20, p=.027). Discussion: Trial 4 of the MIST, a verbal task with a time-based cue that requires participants to complete a pre-specified response after a 15-minute delay, has the potential to be a screener for PM.